2017
DOI: 10.1111/1467-9817.12108
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected poor comprehenders: An investigation of multiple aspects of morphological awareness

Abstract: Poor comprehenders have age-appropriate word reading skills but struggle with understanding what they read. The purpose of this study was to investigate how poor comprehenders perform on multiple aspects of morphological awareness, a skill implicated in reading comprehension. In keeping with current research and theory, we look at three aspects of morphological awareness: morphological structure awareness, morphological analysis and morphological decoding. Using a regression-based approach, we identified 64 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
1
13
0
1
Order By: Relevance
“…Like some previous studies (e.g., Berninger et al, 2010; Deacon & Kirby, 2004; MacKay et al, 2017), the reliability of some of our morphological awareness tasks was low (<.70). This may reflect the wide range of modifying relationships (for compounds) and parts of speech (for compounds, inflections and derivations) that we included as items to provide a comprehensive assessment of this construct.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Like some previous studies (e.g., Berninger et al, 2010; Deacon & Kirby, 2004; MacKay et al, 2017), the reliability of some of our morphological awareness tasks was low (<.70). This may reflect the wide range of modifying relationships (for compounds) and parts of speech (for compounds, inflections and derivations) that we included as items to provide a comprehensive assessment of this construct.…”
Section: Discussionsupporting
confidence: 69%
“…In contrast, no impairments were found on an analogy task measuring inflectional morphology, nor on a sentence completion task to assess morphological knowledge, which provided syntactic support. The relative specificity of poor comprehenders' difficulties to derivational morphology and its task‐dependent nature has been replicated (Tong, Deacon, & Cain, 2014; MacKay, Levesque, & Deacon, 2017), supporting the proposal that derivational knowledge could be a key contributor to comprehension problems. Inflectional knowledge, in contrast, seems to be relatively intact for poor comprehenders, with some evidence that irregular inflections may pose an additional challenge for this group (Adlof & Catts, 2015; Nation, Snowling, & Clarke, 2005).…”
Section: Morphological Awareness and Poor Reading Comprehensionmentioning
confidence: 80%
“…First, poor comprehenders emerge across a wide age range within both alphabetic and non‐alphabetic languages. Specifically, we have shown that reading comprehension difficulties occur in English monolingual children (MacKay, Levesque, & Deacon, ) and adults (Cartwright, Bock, Coppage, Hodgkiss, & Nelson, ), as well as in bilingual L2 children learning either English or French (D'Angelo & Chen, ; Zhang & Shulley, ). Furthermore, poor comprehenders can have co‐occurring difficulties across their two languages.…”
mentioning
confidence: 99%
“…The first relies on discrepancies (Cartwright et al, ; Choi et al, ; Zhang & Shulley, ), which selects children who have reading comprehension scores below a cut point and word reading scores above a cut point, both based on standard scores. The second is the regression‐based approach, which considers other possible reading‐related variables when selecting poor comprehenders (D'Angelo & Chen, ; MacKay et al, ). One challenge with relying solely on reading comprehension and word reading for discrepancies is that it does not take into account other possible causes of reading comprehension difficulties, such as vocabulary.…”
mentioning
confidence: 99%
See 1 more Smart Citation